Language Planning and Language Policy of the Central African Republic in the Monograph of a Central African Researcher - DAVYDOV Artem Vitalievich (Ученые записки Института Африки Российской академии наук, 2025)
Review of the book: Koyt M.M. (2024). Vers un changement linguistique planifié au Centrafrique. Application au modèle glottopolitique. Bangui: Editions Oubangui.